2015
DOI: 10.5376/ijms.2015.05.0015
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of <i>Lepocreadioides orientalis</i> Park, 1939 and <i>Lepocreadioides</i> sp. (Trematoda: Lepocreadiidae) from <i>Psettodes erumei</i> and <i>Sillago sihama</i> from the Iraqi Marine water

Abstract: During the investigation of Psettodes erumei and Sillago sihama two different parasites were detected Lepocreadioides orientalis Park,1939 and Lepocreadioides sp. Fish specimens were collected from the Arabian Gulf during the year 2013. The results indicated that these two parasites are considered as having new hosts viz, P. erumei and S. sihama and as new records in the Iraqi marine fishes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…El-Naffar et al (1992), Kardoush (2003) also reported more than 20 species of digenetic trematode from the Emirati coasts. Some scattered studies were also recorded from other coasts, including Saudi Arabia (Bayoumy et al, 2012) and Oman (Machkevskyi et al, 2014) and Iraq (Bannai, 2002;Bannai and Essa, 2015;Bannai et al, 2005a;2005b).…”
Section: Introductionmentioning
confidence: 99%
“…El-Naffar et al (1992), Kardoush (2003) also reported more than 20 species of digenetic trematode from the Emirati coasts. Some scattered studies were also recorded from other coasts, including Saudi Arabia (Bayoumy et al, 2012) and Oman (Machkevskyi et al, 2014) and Iraq (Bannai, 2002;Bannai and Essa, 2015;Bannai et al, 2005a;2005b).…”
Section: Introductionmentioning
confidence: 99%